Pengaruh inflasi dan nilai tukar rupiah (kurs) terhadap net asset value reksadana syariah yang terdaftar di OJK periode 2012 - 2021 - Delimah Pasaribu, Veta Lidya; Fadila, Muhammad Miftahul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The Effect of Inflation and Rupiah Exchange Rate (Exchange Rate) on Net Asset Value of Sharia Mutual Funds Registered at OJK for the Period January 2012-December 2021, Faculty of Economics and Business Pamulang University, South Tangerang 2022. This study aims to determine the Influence of Inflation and the Rupiah Exchange Rate (Exchange Rate) on the Net Asset Value of Sharia Mutual Funds Registered at OJK for the January 2012-December 2021 Period, either partially or jointly. This study uses quantitative methods and the data used are secondary data. The sample in this study used purposive sampling. The data analysis method used is multiple linear regression analysis, with analysis of the coefficient of determination (R2), t-test, and F-test. Multiple linear regression analysis produces the equation Y = -20,328 - 0.830 Inflation + 2.899 Exchange rate has obtained a coefficient of determination of 0.803 or 80.3% means the coefficient of determination of the net asset value variable is explained by the inflation variable and the rupiah exchange rate (exchange rate) of 80.3% while the remaining 19.7% is explained by other variables outside the study. The results of the t-test showed that the inflation variable (X1) is obtained with t count -10,443 > t table 1,98045 with sig 0.000 < 0.05 then Ho is rejected and Ha is accepted and the exchange rate variable (X2) with t count is 10,631 > t table 1 1,98045 with sig 0.000 <0.05 then Ho is rejected and Ha is accepted, then the inflation variable (X1) has a partial effect on the variable net asset value (Y) and the exchange rate variable (X2) has a partial effect on the net asset value (Y). The results of the F test showed that F counts 232.726 > F table 3.07 and a significance of 0.000 < 0.05, then Ho is rejected and Ha is accepted (Y).